Exploring Children’s Creative Imagination in Conceptual Understanding of the Astronomical World - Gali, Felicita; Venukapalli, Sudhakar (JOURNAL OF INDIAN EDUCATION, 2022)
One of the fascinating traits is that children have inborn potentials and intrinsic qualities that often make them wonder about the terrestrial and celestial worlds and continuously explore the world they experience. Astronomy and space science can a strongly appeal to children. Astronomy is one of the best ways to introduce the spirit of science and creative imagination to children. The current study aims to examine how children’s creative imagination contribute to their understanding of astronomical phenomena. The sample consisted of 36 Grade 9 students from a high school located in Hyderabad, India. An instrument called ‘Test of Creative Imagery Abilities’ (TCIA) was administered to assess children’s ability to draw creative images. To test their knowledge of astronomy, 30 probes on different astronomical topics were administered. Children’s explanations to the probes were categorised as naive, synthetic and scientific. The research was quantitative in nature. Correlational research has shown that children’s conceptual understanding of astronomy is significantly correlated to their creative imagination. The correlation coefficient of the overall score of creative imagination and conceptual understanding in astronomy was found to be 0.482 (p < .05). Though this study had established a moderate but positive relationship between creative imagination and astronomy understanding, the researcher suggests that the introduction of visual creative imagination exercises allow students to gain a better understanding of abstract astronomical phenomena, and teachers should develop strategies that enhance children’s imagination.